In vivo behaviour of some Antithrombin-III-protease and α₁-antitrypsin-protease complexes - Lam, Sheung-Lun Laurence (My University, 1979)
Proteases participate in various aspects of different biological processes to serve purposes as diverse as nutrition and biological controls, all of which are effected by the cleavage of peptide bonds. Nevertheless, proteolysis is an irreversible process because there is no known biological repair mechanism for a broken peptide bond. To ensure that proteases act only beneficially, proteolytic activities are regulated by different control mechanisms, one of which is composed of the natural protease inhibitors. The inhibitors neutralize the proteases by complex formation. The interactions between inhibitors and proteases in vitro have been well documented whereas information on the in vivo behaviours of protease-inhibitor complexes is limited at present. α₂M-protease complexes have been shown to disappear from the circulation extremely rapidly while the clearance of α₁AT-protease complexes is comparatively slow. Thus, it seems, probable that different elimination pathways may exist for different types of protease-inhibitor complexes. The purpose of this study is to examine the in vivo behaviours of some AT Ill-protease complexes, with an attempt to elucidate a probable elimination pathway for such complexes.
Complexes of rabbit, human and rat AT III with rabbit plasmin and of rabbit AT III with rabbit or bovine thrombin were formed from radioactively-labelled proteins and separated from the uncomplexed reactants by preparative electrophoresis. In certain cases, unlabelled proteins were complexed and the complexes were labelled after they had formed. The in vivo behaviour of the complexes was studied in rabbits by the measurement of plasma radioactivity. The integrity of the complexes after injection into the rabbits was monitored by gel filtration of selected plasma samples on Sephadex G-200. Affinity chromatographic columns, such as Sepharose-AT III, -trypsin, -heparin and -lysine were used for the isolation and study of the various components. The stability of AT III-protease complexes under different in vitro conditions was examined by gel filtration and polyacrylamide gel electrophoresis. As a comparison, the complex of rabbit α₁AT with rabbit plasmin was also studied. α₁AT-plasmin complex was separated from uncomplexed materials by affinity chromatography on a Sepharose-lysine column.
The AT III-protease complexes tested were eliminated considerably more slowly than α₂M-protease complexes. The speed of elimination of AT III-protease complexes resembled that of α₁AT-protease complexes. All five combinations of AT III-protease complexes dissociated soon after injection into rabbits, though to variable extents. However, rabbit AT III-plasmin complexes were stable for at least 6 h at 37°C in vitro. Post-complex AT III and post-complex plasmin appeared to have been altered as compared to the corresponding native proteins. Thus post-complex AT III lost more than 80% of its affinity for Sepharoseheparin and this form of the inhibitor no longer bound to Sepharosetrypsin (80% of the control AT III bound to conjugated trypsin). However, post-complex AT III was eliminated only marginally faster than the native AT III and it retained its reactivity with antibodies raised against normal AT III. Post-complex plasmin did not bind to Sepharose-AT III or -Trasylol but about 86% of its ability to bind to Sepharose-Iysie was preserved. Whether the above observations for AT III-protease complexes in rabbits hold true in other species, remains to be established.
Keywords: Medical Sciences; Medical Sciences